Detailed Petrophysical and Geophysical Characterization of Core Samples from the Potential Caprock-reservoir System in the Sulcis Coal Basin (Southwestern Sardinia – Italy). (August 2015) - Fais, Silvana; Ligas, Paola; Cuccuru, Francesco; Maggio, Enrico; Plaisant, Alberto; Pettinau, Alberto; Casula, Giuseppe; Bianchi, Maria Giovanna
Abstract: In this work we present a methodology suitable to identify a caprock-reservoir system for the CO2 storage in the Sulcis Coal Basin (SW Sardinia – Italy). The petrophysical and geophysical characterizations indicate that the potential carbonate reservoir ("Miliolitico" Fm. Auct. ) located at the base of the Eocene stratigraphic sequence in the mining district of the Sulcis Coal Basin, southwestern Sardinia, is heterogeneous but presents suitable reservoir zones for the storage of the CO2. The GPS data analysis indicates that the study area is stable, since it is characterized by a surface crustal deformation smaller than 1 mm/y.